2011
DOI: 10.1038/jhg.2011.73
|View full text |Cite
|
Sign up to set email alerts
|

Association of a synonymous GAT3 polymorphism with antiepileptic drug pharmacoresistance

Abstract: It would be likely that the genetic variants of the GTA3 gene encoding GAT-3, an astrocytic GABA transporter, may alter gammaaminobutyric acid (GABA) neurotransmission in the synaptic cleft in the epileptic brain and cause antiepileptic drugs (AEDs) pharmacoresistance. A candidate gene association analysis with fine mapping was performed to dissect the genetic contributions of GAT3 to AEDs pharmacoresistance. Two independent case sample sets were recruited (Samples 1 and 2), and each set was divided into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Suggestive loci localize to several genes of interest. For example, SLC6A11 is a GABA transporter preferentially expressed in brain (Fagerberg et al, 2014); variation in this gene has been associated with intellectual and behavioral aberrations (Dikow et al, 2014) and resistance to epilepsy pharmacotherapy (Kim et al, 2011). Given the role of the GABAergic system in alcohol response and sensitization (Camarini and Pautassi, 2016; Koob, 2013), the biological plausibility of SLC6A11 is compelling.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestive loci localize to several genes of interest. For example, SLC6A11 is a GABA transporter preferentially expressed in brain (Fagerberg et al, 2014); variation in this gene has been associated with intellectual and behavioral aberrations (Dikow et al, 2014) and resistance to epilepsy pharmacotherapy (Kim et al, 2011). Given the role of the GABAergic system in alcohol response and sensitization (Camarini and Pautassi, 2016; Koob, 2013), the biological plausibility of SLC6A11 is compelling.…”
Section: Discussionmentioning
confidence: 99%
“…This study, together with the study of Carvill et al, suggests that SLC6A1 mutation-positive patients have a combination of intellectual disability, language delay and epilepsy, most frequently associated with MAE syndrome (Johannesen et al, 2018). Regarding GAT-3, the SNP with dbSNP identifier rs2272400 (GAT-3 c.1572 C>T, exon 12) has been associated with antiepileptic drug resistance in a Korean study (Kim et al, 2011). Structurally, the SNP rs2272400 is located in the coding region of GAT-3 on exon 12, however, this does not lead to amino acid changes.…”
Section: Gat-1/gat-3 Polymorphisms and Tlementioning
confidence: 54%
“…In this association study, we analysed the rs2697153 SNP in the GAT-1 gene (SLC6A1) and the rs2272400 SNP in the GAT-3 gene (SLC6A11) in a well-circumscribed cohort of patients with drug-resistant TLE and matched healthy controls. The SNPs were selected based on relevant recent literature (Thoeringer et al, 2009;Kim et al, 2011;Carvill et al, 2015;Johannesen et al, 2018), however, the clinical significance of both SNPs is not yet reported in major databases (dbSNP, gnomAD and ExAC). We observed that the AA GAT-1 genotype was significantly more frequent in patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the reversal of GABA uptake could provide a useful mechanism to curtail seizure propagation. With some exceptions (Xie et al, 2017), single nucleotide polymorphisms in SLC6A11, the gene encoding human GAT3, have been detected in patients with antiepileptic drug resistance (Kim et al, 2011). It is possible that a dysfunction of GAT3 could alter both phasic and tonic GABAergic transmission in the epileptic brain.…”
Section: Physiological Roles Of Gaba Transportersmentioning
confidence: 99%